Numerical simulation of the limiting current for the CE mechanism at a microdisc electrode - Streeter, I; Compton, R (2008)
The finite difference method in conjunction with a conformal mapping technique is used to simulate the diffusion limiting current for three different CE mechanisms at a microdisc electrode. Working surfaces are presented for the variation of the limiting current with a normalised homogeneous kinetic parameter and equilibrium constant. Empirical equations are given to describe the current when the homogeneous equilibrium position lies heavily in favour of the electroinactive species. © 2007 Elsevier B.V. All rights reserved.